Kajian Ilmiah Strategi Pengelolaan Tekno-Stres Tenaga Kerja Dalam Menjaga Stabilitas Produktivitas Di Perusahaan - Wahyu Satria Pamungkas; Lexy Tarumanegoro Pangalila; Fardhan Hajid Santoso; Sabil Nur Komarudin (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
Digital transformation within contemporary employment relations has fundamentally altered organizational work patterns while simultaneously generating complex psychosocial risks, particularly technostress arising from continuous connectivity and excessive digital demands. This study examined the juridical dimensions of technostress management and its implications for maintaining workforce productivity stability through normative legal research using conceptual, statutory, and doctrinal approaches. The findings indicate that existing Indonesian labor regulations remain predominantly oriented toward conventional physical labor protection and have not comprehensively accommodated digital psychosocial hazards, including the absence of explicit regulation concerning the right to disconnect, proportional digital surveillance, and digital mental health protection. Regulatory reconstruction toward digital occupational safety is therefore required to establish adaptive, human-centered, and sustainable labor governance within the contemporary digital workplace ecosystem.